New conservation laws and exact solutions of the special case of the fifth-order KdV equation - Akbulut, Arzu; Kaplan, Melike; Kaabar, Mohammed Khalid Awad (Elsevier BV, 2022)
The current study deals with the Kaup-Kupershmidt (KK) equation to construct formal Lagrangian, conservation laws, and exact solutions. KK is basically a special case of the 5th-order KdV equation. The conservation laws obtained by using the conservation theorem are trivial conservation laws. In addition, exact solutions are found via the modified simple equation (MSE) method. For a suitable value of solutions, the 3D surfaces have been plotted using MAPLE. These plots giving novel exact solutions are made to reveal important wave characteristics. Our obtained results in this work concerning our investigated equation are essential to explain many physical and oceanographic applications involving ocean gravity waves and many other related phenomena.
Keywords: Ocean engineering; TC Hydraulic engineering. Ocean engineering; C15; F10; QA Mathematics; S10; TC1501-1800